Factors Affecting Villagers Participation in Community Environment Development - Praneetham, Chuleewan; Thiengkamol, Nongnapas; Thathong, Kongsak; Thiengkamol, Tanarat (Richtmann Publishing, 2012)
The objectives of this research were to develop a prototype network of community environment with integration of environmental education principle and the principle of self-sufficiency economy and study factors affecting of villagers participation in community environment development in Khon Kaen Province, Thailand. The population was villagers in the Khon Kaen Province, Thailand. The simple random sampling technique was employed to collect 400 villagers for this research. The questionnaire was used as research instrument for data collection. The content and structural validity were determined by Item Objective Congruent (IOC) with 5 experts in the aspects of environmental education, psychology, social research methodology and philosophy of self-sufficiency economy. The reliability was determined by Cronbach’s Alpha. Reliability of knowledge about environment, awareness, attitude towards environment, behavior towards environment and self-sufficiency economy practice and the whole questionnaire were 0.884, 0.874, 0.893, 0.900, 0.942 and 0.934 respectively. The descriptive statistics used were frequency, percentage, mean and standard deviation. The inferential statistics used was the Canonical Correlation Analysis for statistical analysis.The results revealed that the best model of canonical correlation for the prototype village of sufficiency economy and the ordinary village sample group were the models had canonically correlation with .36136 and .39126 respectively between the set of independent variable of canonical correlation between knowledge, awareness and attitude towards environment and the set of dependent variables included behavior towards environment and self-sufficiency economy practice.